Pure ethnic gaps in educational attainment and school to work transitions. When do they arise? - Baert, Stijn; Cockx, Bart (Munich, 2013)
"This article decomposes the observed gaps in educational attainment and school-to-work transitions between grandchildren of natives and immigrants in Belgium into (i) differences in observed family endowments and (ii) a residual “pure ethnic gap”. It innovates by explicitly taking delays in educational attainment into account, by identifying the moments at which the pure ethnic gaps arise, by disentangling the decision to continue schooling at the end of a school year from the achievement within a particular grade, and by integrating the language spoken at home among observed family endowments. The pure ethnic gap in educational attainment is found to be small if delays are neglected, but substantial if not and for school-to-work transitions. It is shown that more than 20% of the pure ethnic gap in graduating from secondary school without delay originates in tenth grade. Language usage explains only part of the gap in school-to-work transitions for low educated."